2009
DOI: 10.1111/j.1742-4658.2008.06831.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathways involved in testicular germ cell apoptosis induced by H2O2in vitro

Abstract: H2O2 induces apoptosis in variety of cells; however, the sensitivities of testicular germ cells to H2O2 are not known. In the present study, H2O2, at concentrations in the range 1–10 μm, was found to induce apoptosis in testicular germ cells in vitro. Following 1 h of treatment with 10 μm H2O2, a 10‐fold rise in the percentage of apoptotic cells was observed. Induction of germ cell apoptosis was directly associated with a significant (P < 0.01) increase in lipid peroxidation and a concomitant decrease in super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 46 publications
1
80
1
Order By: Relevance
“…Our findings are similar to several reports from other groups with respect to the mechanisms of apoptosis in testicular germ cells induced by ischemia, irradiation, and excitotoxicity. For example, Maheshwari et al (2009) demonstrated that H 2 O 2 -elicited apoptosis of testicular germ cells is associated with activation of the p53, Bax, Fas/Fasl, and a simultaneous decrease in the Bcl-2 expression. It was also observed by Chaki et al (2006) that an elevated expression of cell death effector Bax may contribute to the rat germ cell apoptosis with estradiol-3-benzoate administered.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to several reports from other groups with respect to the mechanisms of apoptosis in testicular germ cells induced by ischemia, irradiation, and excitotoxicity. For example, Maheshwari et al (2009) demonstrated that H 2 O 2 -elicited apoptosis of testicular germ cells is associated with activation of the p53, Bax, Fas/Fasl, and a simultaneous decrease in the Bcl-2 expression. It was also observed by Chaki et al (2006) that an elevated expression of cell death effector Bax may contribute to the rat germ cell apoptosis with estradiol-3-benzoate administered.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the Bcl-2 family proteins are either germ cell survival or death modulators [Knudson et al 1995;Mahmoud et al 2009;Yan et al 2000]. Functions of the Bcl-2 related proteins comprise pro-apoptotic (Bax, Bad, and Bid) and anti-apoptotic (Bcl-2, Bcl-xL) proteins [Knudson et al 1995;Maheshwari et al 2009;Yamamoto et al 2000]. Induction of Bax acute stress may promote changes in mitochondrial membrane permeability and release cytochrome C into the cytosol [Blatt and Glick 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is known that the testes extrinsic apoptotic pathway involves the activation of the Fas receptor and its ligand (FasL), expressed by Sertoli, spermatocyte, and Leyding cells. Once bound to its ligand, Fas can trigger the apoptotic event [Pentikainen et al 1999;Porcelli et al 2006], by a caspase-8 dependent mechanism [Maheshwari et al 2009;Said et al 2004]. Caspase-8 is required for caspase-3 cleavage [Said et al 2004] that is necessary to trigger apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For heat stress, cells were incubated at 43 8C for 20 min (Saitoh & Hinchey 2000). Experiments with low doses of H 2 O 2 were performed for 1 h (Maheshwari et al 2009). …”
Section: Stress and Drug Treatmentmentioning
confidence: 99%